Recombinant FXIII (rFXIII-A2) Prophylaxis Prevents Bleeding and Allows for Surgery in Patients with Congenital FXIII A-Subunit Deficiency - Carcao, Manuel; Altisent, Carmen; Castaman, Giancarlo; Fukutake, Katsuyuki; Kerlin, Bryce A.; Kessler, Craig; Lassila, Riitta; Nugent, Diane; Oldenburg, Johannes; Garly, May-Lill; Rosholm, Anders; Inbal, Aida (Thrombosis and Haemostasis, 2018)
Recombinant factor XIII-A2 (rFXIII-A2) was developed for prophylaxis and treatment of bleeds in patients with congenital FXIII A-subunit deficiency. mentor™2 (NCT00978380), a multinational, open-label, single-arm, multiple-dosing extension to the pivotal mentor™1 trial, assessed long-term safety and efficacy of rFXIII-A2 prophylaxis in eligible patients (patients with severe [<0.05 IU/mL] congenital FXIII subunit A deficiency) aged ≥6 years. Patients received 35 IU/kg rFXIII-A2 (exact dosing) every 28 ± 2 days for ≥52 weeks. Primary endpoint was safety (adverse events including immunogenicity); secondary endpoints were rate of bleeds requiring FXIII treatment, haemostatic response after one 35 IU/kg rFXIII-A2 dose for breakthrough bleeds and withdrawals due to lack of rFXIII-A2 efficacy. Steady-state pharmacokinetic variables were also summarized. Elective surgery was permitted during the treatment period. Sixty patients were exposed to rFXIII-A2; their median age was 26.0 years (range: 7.0–77.0). rFXIII-A2 was well tolerated without any safety concerns. No non-neutralizing or neutralizing antibodies (inhibitors) against FXIII were detected. Mean annualized bleeding rate (ABR) was 0.043/patient-year. Mean spontaneous ABR was 0.011/patient-year. No patients withdrew due to lack of efficacy. Geometric mean FXIII trough level was 0.17 IU/mL. Geometric terminal half-life was 13.7 days. rFXIII-A2 prophylaxis provided sufficient haemostatic coverage for 12 minor surgeries without the need for additional FXIII therapy; eight procedures were performed within 7 days of the patient's last scheduled rFXIII-A2 dose, and four were performed 10 to 21 days after the last dose.
Keywords: recombinant FXIII-A2; safety; congenital FXIII deficiency; prophylaxis; surgery